What Goes Up, Must Come Down: A State-of-the-Art Electronic Health Record Downtime and Uptime Procedure in a Metropolitan Health Setting - Lyon, Rachael; Jones, Aaron; Burke, Rosemary; Baysari, Melissa T. (Applied Clinical Informatics, 2023)
Background Electronic health records (EHRs) are used at most hospitals around the world, and downtime events are inevitable and common. Downtime represents a risky time for patients because patient information and critical EHR functionality are unavailable. Many institutions have used EHRs for years, with health professionals less likely to be familiar or comfortable with paper-based processes, resulting in an increased risk of errors during downtimes. There is currently limited guidance available on how to develop and operationalize downtime procedure at a local level. In this paper, we fill this gap by describing our state-of-the-art downtime and uptime procedure and its evaluation.Method A district-wide downtime and uptime procedure was revised and standardized based on lessons learned from other health care organizations. The procedure outlines downtime and uptime preparations including downtime drills, downtime viewer auditing, and downtime education; downtime response including activating downtime and tracking patient changes; and uptime recovery including medication reconciliation and uptime documentation.Implementation We implemented our new procedure across the district during an 8-hour planned downtime. A district downtime planning committee was formed, and a virtual command center was established to coordinate the downtime and uptime events. During downtime and uptime, onsite support was provided by the district's health informatics teams and clinicians. Data recovery was completed safely and efficiently with the revised uptime process. Following the event, we gathered staff feedback and reflections on implementing the procedure which highlighted its success but also revealed some areas for further improvement.Conclusion In this paper, we describe a state-of-the-art EHR downtime and uptime procedure and lessons learned from its implementation. The implementation was successful with staff well prepared and information reconciled efficiently ensuring safe continuity of care. It was only through extensive planning, significant commitment, and engagement of all stakeholders that this outcome was possible.
Keywords: electronic health records; downtime; hardware/software failure